Optimal control based on nonlinear conjugate gradient method in cardiac electrophysiology - Ng, Kin Wei, 1985-; Rohanin Ahmad, supervisor; Fakulti Sains (2013)
Thesis (Ph.D (Matematik)) - Universiti Teknologi Malaysia, 2013